2004
DOI: 10.1152/ajpheart.00481.2003
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen suppresses IL-1β-mediated induction of COX-2 pathway in rat cerebral blood vessels

Abstract: Ospina, Jose A., Holly N. Brevig, Diana N. Krause, and Sue P. Duckles. Estrogen suppresses IL-1␤-mediated induction of COX-2 pathway in rat cerebral blood vessels. Am J Physiol Heart Circ Physiol 286: H2010-H2019, 2004. First published December 18, 2003 10.1152/ajpheart.00481.2003.-Interleukin (IL)-1␤ is a potent inducer of inflammatory prostaglandins, which are important mediators of vascular response to cerebral injury, whereas estrogen reduces brain injury in models of ischemic stroke. Thus we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 50 publications
8
66
0
1
Order By: Relevance
“…Inducible NO synthase expression is attenuated by E 2 , though the latter failed to alter NF-B activation in primary rat microglia and N9 microglial cell lines (15). Ospina et al (39) have reported that estrogen decreases the inflammatory response to IL-1 in the brain in OVX animals and that sex hormone replacement in OVX rats attenuated LPS fever (40), but it potentiated IL-1␤-induced fever and cyclooxygenase-2 expression in the brain (41). E 2 was also found to significantly prevent LPS-induced microglial reactivity in an ER␣-dependent manner (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Inducible NO synthase expression is attenuated by E 2 , though the latter failed to alter NF-B activation in primary rat microglia and N9 microglial cell lines (15). Ospina et al (39) have reported that estrogen decreases the inflammatory response to IL-1 in the brain in OVX animals and that sex hormone replacement in OVX rats attenuated LPS fever (40), but it potentiated IL-1␤-induced fever and cyclooxygenase-2 expression in the brain (41). E 2 was also found to significantly prevent LPS-induced microglial reactivity in an ER␣-dependent manner (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogenic abrogation of inflammation initiated by TNF-␣ is perhaps the most consistent of these effects and may be critical for linking infection to cardiovascular disease as TNF-␣ increases transiently even with low levels of lipopolysaccharide challenge (Jayachandran et al, 2007). Interestingly, in rats estrogen has been shown to suppress vascular inflammatory responses to IL-1␤ and lipopolysaccharide treatments, and this response has also been shown to vary through the estrous cycle (Galea et al, 2002;Ospina et al, 2004;Sunday et al, 2006). An intriguing result is that this anti-inflammatory effect of estrogen is lost in older female animals (Miller et al, 2004a;Sunday et al, 2007).…”
Section: A Inflammationmentioning
confidence: 99%
“…Known inhibitors of COX-2 include estrogens, antioxidants, and p53 (31)(32)(33). The presence of active p53 in particular has been shown to decrease both the mRNA and protein levels of Cox-2 in mouse embryo fibroblasts (33).…”
mentioning
confidence: 99%